Calcareous benthic foraminifera from the upper central Peruvian margin: control of the assemblage by pore water redox and sedimentary organic matter - Cardich, J (2015)
The research was granted by the ‘Cátedra CONCYTEC en Ciencias del Mar’, sponsored by the Peruvian National Council of Science and Technology and the Universidad Peruana Cayetano Heredia, Master Program of Marine Sciences, and by the Peruvian Marine Research Institute (IMARPE) project INIOX. It was also supported by collaborative projects between the Institut de la Recherche pour le Développement (IRD) and IMARPE: LMI DISCOH and Chaire Croisée PROSUR.